Insecticide-impregnated ear tags for range cattle - Lynch, G.L.; Zoellner, K.O.; Broce, A.B.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
When both cows and calves were double-tagged (one tag per ear) with ear tags impregnated with fenvalerate (Ectrin) or permethrin (Atroban), the calves gained faster (P<.01) than when neither cows nor calves were tagged. Double-tagged yearling heifers gained faster (P<.05) than did heifers without tags. When all cows had been double-tagged, tagging the calves did not increase calf weight gain.
Keywords: Beef; Insecticide-impregnated ear tags; Heifers; Gain